Increase in Adult Patients with Varicella Zoster Virus–Related Central Nervous System Infections, Japan - Ayami Yoshikane; Hiroki Miura; Sayuri Shima; Masaaki Matsunaga; Soichiro Ishimaru; Yuki Higashimoto; Yoshiki Kawamura; Kei Kozawa; Akiko Yoshikawa; Akihiro Ueda; Atsuhiko Ota; Hirohisa Watanabe; et al. (Emerging Infectious Diseases)
An increase in the number of herpes zoster patients has been reported since universal varicella immunization was introduced, perhaps because of reduced opportunities for varicella patients to experience the natural booster effect caused by reexposure. We investigated recent trends of varicella zoster virus (VZV)–related central nervous system (CNS) infections at a university hospital in Japan. We enrolled patients with suspected CNS infection during 2013–2022 and tested cerebrospinal fluid samples by real-time PCR for DNA from 7 human herpesviruses. VZV DNA was the most commonly detected in 62 (10.2%) of 615 patients. Kulldorff’s circular spatial scan statistics demonstrated a significant temporal cluster of patients with VZV-related CNS infections during 2019–2022 (p = 0.008). Among persons with such infections, the percentage with aseptic meningitis was significantly higher during 2019–2022 (86.8%), when the temporal cluster of cases occurred, than during 2013–2018 (50.0%) (p = 0.0029).